Maximizing Youtube for EFL Listening Education: Strategies and Challenges (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of digital resources in English as a Foreign Language (EFL) education is becoming increasingly important. Among these tools, YouTube has emerged as a prominent resource for enhancing listening skills. This paper delves into the strategies and challenges associated with maximizing YouTube for EFL listening education. This study employs a qualitative research design utilizing library research methodology to explore the strategies and challenges of maximizing YouTube for EFL listening education. The study discussed the significant positive effect of using YouTube videos on students’ listening comprehension performance. The results highlight the distinct benefits of YouTube in improving listening skills and encouraging the creation of creative educational media, even though the study’s primary focus is on English language instruction, indicating a need for more extensive research across a range of educational sectors. To completely comprehend and take advantage of YouTube’s educational potential, future research should keep examining these dynamics.